Control of a Second-Order Electromechanical System under Mixed Constraints - Avetisyan, V. V. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
For a system simulating the dynamics of a single-link electromechanical manipulator, the problem of constructing a control voltage and determining the areas of final states is solved, the transition to any point of which from the initial state of rest using the constructed control occurs in a finite time without violating the specified restrictions on the voltage and heat release power in the winding of the rotor of the electric motor․ Для системы, моделирующей динамику однозвенного электромеханического манипулятора, решается задача построения управляющего напряжения и определения областей конечных состояний, переход в любую точку которых из начального состояния покоя с помощью построенного управления происходит за конечное время без нарушения заданных ограничений на напряжение и мощность тепловыделения в обмотке ротора электродвигателя. Մեկ օղակով էլեկտրամեխանիկական մանիպուլյատորի դինամիկան նկարագրող համակարգի համար լուծվում է ղեկավարող լարման և վերջնական վիճակների տիրույթների կառուցման խնդիրը, որոնց յուրաքանչյուր կետ սկզբնական հանգստի վիճակից համակարգի տեղափոխումը կառուցված ղեկավարման օգնությամբ իրականացվում է վերջավոր ժամանակում՝ առանց լարման և էլեկտրաշարժիչի ռոտորի փաթույթի հզորության վրա դրված տրված սահմանափակումների խախտման։
Keywords: Mechanics